2017
DOI: 10.1002/bdm.2071
|View full text |Cite
|
Sign up to set email alerts
|

Spendthrifts and Tightwads in Childhood: Feelings about Spending Predict Children's Financial Decision Making

Abstract: Adults differ in the extent to which they find spending money to be distressing; "tightwads" find spending money painful, and "spendthrifts" do not find spending painful enough. This affective dimension has been reliably measured in adults and predicts a variety of important financial behaviors and outcomes (e.g., saving behavior and credit scores). Although children's financial behavior has also received attention, feelings about spending have not been studied in children, as they have in adults. We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
8
2
Order By: Relevance
“…To the contrary, in our own research, we find that young children, too, vary on the tightwad/spendthrift dimension (Smith, Echelbarger, Gelman, & Rick, 2018). We have found that children as young as 5 years can accurately report on their spending orientation, that these feelings accord with parent reports, and that these feelings have predictive utility (i.e., they predict whether children will spend or save $1 we give them; Smith et al, 2018). Thus, experience with money and spending alone cannot explain how these feelings develop-though, without examining these "adult" responses in children, we would be left with an incomplete understanding of their origins.…”
Section: What Can Development Tell Us?contrasting
confidence: 85%
See 1 more Smart Citation
“…To the contrary, in our own research, we find that young children, too, vary on the tightwad/spendthrift dimension (Smith, Echelbarger, Gelman, & Rick, 2018). We have found that children as young as 5 years can accurately report on their spending orientation, that these feelings accord with parent reports, and that these feelings have predictive utility (i.e., they predict whether children will spend or save $1 we give them; Smith et al, 2018). Thus, experience with money and spending alone cannot explain how these feelings develop-though, without examining these "adult" responses in children, we would be left with an incomplete understanding of their origins.…”
Section: What Can Development Tell Us?contrasting
confidence: 85%
“…One possibility is that such differences emerge from years of experience handling one's own finances, such that children start out as spendthrifts and only gradually over time do we see some individuals shifting toward tightwaddism. To the contrary, in our own research, we find that young children, too, vary on the tightwad/spendthrift dimension (Smith, Echelbarger, Gelman, & Rick, ). We have found that children as young as 5 years can accurately report on their spending orientation, that these feelings accord with parent reports, and that these feelings have predictive utility (i.e., they predict whether children will spend or save $1 we give them; Smith et al., ).…”
Section: What Can Development Tell Us?contrasting
confidence: 84%
“…Research has examined how money is managed, how consumption priorities are established and how gratification is postponed within households. Concomitantly, investigation on how children are taught by their families about consumption and money has also been undertaken, emphasis being put in educational differentials stemming from economic and social capital (Luhr, 2018;Smith, Echelbarger, Gelman, & Rick, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the extent to which adults (and even children) may find spending money to be painful, can be used to predict key financial behaviors and outcomes (e.g., credit scores, savings behavior, etc.) (Smith et al, 2018). Which in turn may help explain why consumers' financial health can be predicted using their aversion to high-cost financial products and services (Greenberg et al, 2020).…”
Section: Financial Resiliency and Matched Savings Programsmentioning
confidence: 99%